Social Development - Parke, Ross D., author 450250; Roisman, Glenn I., author 655021; Rose, Amanda J. (Amanda Janel), 1971-, author 655022; John Wiley & Sons (Online service) 647106 (Hoboken, NJ : John Wiley & Sons, Inc.)
Social Development provides a comprehensive introduction to the multiple factors that shape a child’s behavior, interaction with others, feelings about themselves, and how and why behaviors change over time. Delving into the biological, cognitive, and perceptual aspects of development and their influence on behavior, socialization, and self-image, this text also recognizes the significance of cultural and societal distinctions by emphasizing the value of context and identifying cultural variation’s role in social development. Special pedagogical features in each chapter enhance the learning experience and promote student understanding: counter-intuitive examples cases challenge reader assumptions, coverage of extreme cases tell the story behind historical advancements, and profiles of current leaders in the field highlight the many paths to a career in social development. With a focus on real-world application, coupled with coverage of cutting-edge methodologies and the latest research findings, this book gives students a strong, highly relevant foundation in core concepts and practices central to the study of social development.